Level of Interprofessional Collaboration in Hospital Intensive Care Unit (ICU) - Indri Permanasari; Puput Oktamianti (Syntax Literate, 2023)
Interprofessional collaboration plays a crucial role in the intensive care unit (ICU) setting. It involves healthcare professionals from different disciplines working together to provide holistic care to critically ill patients. In past decades research about effective collaboration has shown that it requires a combination of individual attitudes, team dynamics, and institutional factors. Individual attitudes encompass respect, trust, and open communication among team members. It is essential for professionals to value each other's expertise and contribute their unique perspectives to optimize patient outcomes. Team dynamics involve effective leadership, clear roles and responsibilities, and shared decision-making. When teams function cohesively, they can efficiently address complex ICU challenges. Institutional factors, such as organizational culture, policies, and resources, significantly influence interprofessional collaboration. Supportive environments that encourage collaboration through education, training, and interdisciplinary meetings foster a culture of teamwork. Ultimately, successful interprofessional collaboration in the ICU leads to improved patient safety, enhanced clinical outcomes, and better overall healthcare delivery. By leveraging the diverse skills and knowledge of healthcare professionals, ICU teams can provide comprehensive care that meets the complex needs of critically ill patients.